The CNAO dose delivery system for modulated scanning ion beam radiotherapy. Issue 1 (23rd December 2014) - Giordanengo, S.; Garella, M. A.; Marchetto, F.; Bourhaleb, F.; Ciocca, M.; Mirandola, A.; Monaco, V.; Hosseini, M. A.; Peroni, C.; Sacchi, R.; Cirio, R.; Donetti, M.
Abstract : Purpose: This paper describes the system for the dose delivery currently used at the Centro Nazionale di Adroterapia Oncologica (CNAO) for ion beam modulated scanning radiotherapy. Methods: CNAO Foundation, Istituto Nazionale di Fisica Nucleare and University of Torino have designed, built, and commissioned a dose delivery system (DDS) to monitor and guide ion beams accelerated by a dedicated synchrotron and to distribute the dose with a full 3D scanning technique. Protons and carbon ions are provided for a wide range of energies in order to cover a sizable span of treatment depths. The target volume, segmented in several layers orthogonally to the beam direction, is irradiated by thousands of pencil beams which must be steered and held to the prescribed positions until the prescribed number of particles has been delivered. For the CNAO beam lines, these operations are performed by the DDS. The main components of this system are two independent beam monitoring detectors, called BOX1 and BOX2, interfaced with two control systems performing the tasks of real‐time fast and slow control, and connected to the scanning magnets and the beam chopper. As a reaction to any condition leading to a potential hazard, a DDS interlock signal is sent to the patient interlock system which immediately stops the irradiation. The essential tasks and operations performed by the DDS are described following the data flow from the treatment planning system through the end of the treatment delivery. Results: The ability of the DDS to guarantee a safe and accurate treatment was validated during the commissioning phase by means of checks of the charge collection efficiency, gain uniformity of the chambers, and 2D dose distribution homogeneity and stability. A high level of reliability and robustness has been proven by three years of system activity needing rarely more than regular maintenance and working with 100% uptime. Four identical and independent DDS devices have been tested showing comparable performances and are presently in use on the CNAO beam lines for clinical activity. Conclusions: The dose delivery system described in this paper is one among the few worldwide existing systems to operate ion beam for modulated scanning radiotherapy. At the time of writing, it has been used to treat more than 350 patients and it has proven to guide and control the therapeutic pencil beams reaching performances well above clinical requirements. In particular, in terms of dose accuracy and stability, daily quality assurance measurements have shown dose deviations always lower than the acceptance threshold of 5% and 2.5%, respectively.